The development strategy of durian fruit-based ecotourism: A case study of Rancamaya Village in Bogor, Indonesia - Liza Indina; Sodikin; Lina Warlina (Universitas Pakuan, 2025)
Legok Petir place in Rancamaya Village, South Bogor District, has a strategic role in efforts to improve the surrounding community's welfare sustainably. With a long history of durian fruit, Rancamaya has the nickname of